Analysis of the Socio-Economic Characteristics of the Skipper in Barrang Lompo Island Makassar City - Nyompa, Sukri; Maru, Rosmini; Arfan, Amal; Saputro, Alief; Rabi'ah, Rabi'ah (UNIVERSITAS NEGERI MAKASSAR, 2021)
Barrang Lompo Island is one of the islands located on the west coast of Losari Makassar City with different socio-economic characteristics of the population. The purpose of this study is to analyze the socio-economic characteristics of the skipper and their contribution to the household income of the skipper's family on the island of Barrang Lompo. The analysis of this study used descriptive statistics. The data used are primary and secondary data presented in the form of percentages, cross tables, and pictures. The results of this study can be seen by gender, age, education, income, ethnicity, regional origin, number of crew employed on the ship, number of dependents and the contribution of income. However, the government needs to take strategic policies to improve the welfare of fishermen on Barrang Lompo Island in particular and the population in general.